Azithromycin in high‐risk, refractory chronic rhinosinusitus after endoscopic sinus surgery and corticosteroid irrigations: a double‐blind, randomized, placebo‐controlled trial. Issue 4 (15th September 2020) - Maniakas, Anastasios; Asmar, Marc‐Henri; Renteria, Axel Eluid; Nayan, Smriti; Alromaih, Saud; Endam, Leandra Mfuna; Sampalis, John Sam; Desrosiers, Martin
Abstract : Background: Refractory chronic rhinosinusitis (CRS) remains a significant burden for patients, often leaving them with few therapeutic options that provide low‐morbidity, long‐term, and meaningful symptomatologic and endoscopic disease improvement. Macrolides have long been thought to offer both an immunomodulatory and antimicrobial effect. Our objective was to evaluate the efficacy of low‐dose, long‐term azithromycin in a carefully selected high‐risk population failing appropriate medical therapy of budesonide nasal irrigations (BNIs) and endoscopic sinus surgery (ESS). Methods: A double‐blind, randomized, placebo‐controlled trial was completed in a single tertiary‐care center assessing the addition of 250 mg azithromycin, 3 times per week for 16 weeks, in adults failing ESS and high‐volume BNIs. Associated comorbidities, as well as symptomatologic, microbiologic, and serologic values, were systematically collected. Results: A total of 128 patients were enrolled and underwent ESS followed by BNI. At the 4‐month post‐ESS visit, 48 patients showed disease persistence and were randomized to azithromycin or placebo. Overall, azithromycin, when compared with placebo, did not show a statistically significant difference in disease clearance (54% vs 33%, respectively; p = 0.146), although patients with disease clearance who were on azithromycin showed significantly better 22‐item Sino‐Nasal Outcome Test score improvements than patients on placebo (18 vs −0.9, respectively; p = 0.046). In a subgroup analysis excluding aspirin‐exacerbated respiratory disease (AERD) patients, azithromycin significantly improved disease clearance when compared with placebo (71% vs 35%, respectively; p = 0.031), with a number needed to treat of 3 (2.8). Conclusion: Low‐dose azithromycin is a therapeutic option with few side effects. Its use can show favorable clinical outcomes in this difficult‐to‐treat population, especially if patients are AERD‐negative.